The Effect of Service Quality, Product Quality and Brand Image on Customer Loyalty Through Customer Satisfaction Mediation at Mie Gacoan Surakarta - Nabila Zulfa Nur Latifa; Edy Purwo Saputro (Jurnal Economic Resource, 2026)
Customer satisfaction acts as a mediating variable at Mie Gacoan Surakarta. This study examines the influence of service quality, product quality, and brand image on customer loyalty. The background of this study is based on conflicting results from previous investigations regarding the relationship between these factors. The quantitative methodology of this study is based on partial least squares (PLS) and structural equation modeling (SEM). A closed questionnaire was sent to 165 Mie Gacoan Surakarta customers who had made purchases to collect primary data. These findings show that customer satisfaction is visibly and profitably influenced by brand image, product quality, and service quality. Client loyalty is not overly affected by these three factors. On the other hand, client satisfaction has been shown to have a substantial and beneficial impact on customer loyalty, serving as a mediator between brand image, service quality, and product quality. Therefore, at Mie Gacoan Surakarta, ensuring client satisfaction is essential to building client loyalty. The conclusion of this study highlights the importance of improving the quality of goods and services while strengthening brand recognition, ensuring customers remain happy and loyal amid fierce competition in the culinary sector.